Bone Magnesium Pools in Uremia - Alfrey, Allen C. (1973)
Bone magnesium pools were studied in vitro in bone specimens obtained from control subjects, from patients with chronic renal failure before and after renal transplantation, and in a patient with chronic hypomagnesemia. 30% of bone magnesium is in a surface limited pool present either within the hydration shell or else on the crystal surface. The larger fraction of bone magnesium was shown not to be associated with bone matrix but rather to be an integral part of the bone crystal. With incineration this pool was mobilized at the same temperature that sudden enlargement of bone crystal size occurred. It is suggested that heating causes surface calcium to displace magnesium from the apatite crystal. Both magnesium pools are increased in patients with chronic renal failure. The major factor determining magnesium concentration in bone would appear to be the serum magnesium level. Following renal transplantation, in association with the fall in serum magnesium, surface magnesium was within the normal range; whereas, residual magnesium was not different from the other urenic bones. Both magnesium pools were significantly reduced in a patient with chronic hypomagnesemia. The in vitro studies would suggest that surface magnesium should rapidly reflect changes in serum magnesium levels, whereas, the deeper magnesium pool is probably deposited at time of bone formation with mobilization being dependent upon the resorptive processes. Since magnesium can influence crystal size and stability it seems possible that excess bone magnesium may play a role in renal osteodystrophy.